Kepadatan Siput Terebralia palustris (Jantan dan Betina) pada Ekosistem Mangrove Pulau Pannikiang - Andi Nur Samsi; Rusmidin Rusmidin (Unversitas Muhammadiyah Mataram, 2022)
Abstract: The snail Terebralia palustris is a species of snail that lives in the mangrove ecosystem on Pannikiang Island, Barru Regency, South Sulawesi. This snail is known as